Electrochemistry Study on PVC-LiClO4 Polymer Electrolyte Supported by Bengkulu Natural Bentonite for Lithium Battery - Ghufira Ghufira; Sal P Yudha; Eka Angasa; Jhoni Ariesta (Graduate Program of Syiah Kuala University, 2012)
Abstract – In this research bentonite was used as filler to produce polymer electrolyte (PVCLiClO4). Some weight variation of bentonite have been made by addition, such as 0% wt/wt; 5% wt/wt ; 10% wt/wt ; 15% wt/wt ; 20% wt/wt ; and 25% wt/wt of bentonite to the mixture of 0,5 gram of PVC and 0,125 gram of LiClO4. Ionic conductivity of polymer electrolyte was tested using impedance spectroscopy. The result of the research was showed that a mixture of PVCBentonite( 10% wt/wt)-LiClO4 gives the highest ionic conductivity (4,86 x 10-3 S.Cm-1). This result indicated that the presence of natural bentonite can be used as a filler in the current composite polymer electrolyte and can increase the ionic conductivity of the polymer electrolyte.